Pacemaker and Atrioventricular Junction Ablation in Patients With Atrial Fibrillation—A Systematic Review of Systematic Review and Meta-Analysis - Zhang, Chi; Wang, Xi-Ying; Lou, Lian; Zhang, Xuan; Chen, Le-Le; Chen, Yu-Xiao; Yang, Jian (Frontiers in Cardiovascular Medicine, 2022)
Background Pacing has been recommended as the IA class for heart failure patients in sinus rhythm and prolonged QRS duration. The benefit of pacemaker(mainly cardiac resynchronization therapy(CRT)) in atrial fibrillation(AF) patients and whether atrioventricular junction (or nodal) ablation(AVAB) can further improve the prognosis of these patients compared with those treated with medicine as a rate control strategy are still controversial. Method and results We performed an overview of systematic reviews and meta-analyses investigating the role of pacemaker and AVAB in patients with AF. Pubmed, Embase and Medline databases are searched for eligible systematic reviews and meta-analyses. Mortality, left ventricular ejection fraction(LVEF), clinical evaluations, including NYHA class, 6 minutes walk distance(6MWD) and quality of life by specific questionnaire, and response to cardiac resynchronization therapy are the main outcomes observed in our overview. The quality of included reviews is assessed via the AMSTAR-2(Assessing the Methodological Quality of Systematic Reviews) tool which included 16 items. Fifteen systematic reviews or meta-analyses are included in our overview and nine relevant conference abstracts are excluded from our overview for the missing data of their full-text. In our overview, patients with AF have a higher rate of all-cause mortality than patients with sinus rhythm(SR) whereas the application of AVAB can reduce the all-cause mortality in AF patients. Although the function improvement in SR patients is superior to AF patients, AVAB can prolong the 6MWD and reduce the non-response rate to CRT in AF patients. Conclusion AF is associated with higher all-cause mortality in patients with CRT implantation. Although there is no evidence of benefit for the practice of AVAB, AVAB is noted to be associated with lower all-cause mortality and improved 6WMD in AF patients.